LGBTQ young adult fiction : a critical survey, 1970s-2010s - Town, Caren J., 1957- (McFarland & Company, Inc., Publishers, 2017)
"The author explores a selection of recent novels--many of which may be new to readers--and places them in the wider contexts of LGBTQ literature and history. Chapters discuss a range of topics, including the relationship of Queer Theory to literature, LGBTQ families, and recent trends in utopian and dystopian science fiction"- Resumé vydavatel
Keywords: homosexualita a literatura -- dějiny -- 1971-2010 -- Spojené státy americké; sexuální identita; sexuální menšiny; literatura pro mládež -- 1971-2010 -- dějiny -- Spojené státy americké; americký román; homosexuality and literature -- history -- 1971-2010 -- United States; sexual identity; sexual minorities; juvenile literature -- history -- 1971-2010 -- United States; American fiction; queer; monografie; monographs